Exportins can inhibit major mitotic assembly events in vitro: membrane fusion, nuclear pore formation, and spindle assembly - Matthew S. Nord; Cyril Bernis; Sarah Carmona; Dennis C. Garland; Anna Travesa; Douglass J. Forbes (Nucleus, 2020)
Xenopus egg extracts are a powerful in vitro tool for studying complex biological processes, including nuclear reconstitution, nuclear membrane and pore assembly, and spindle assembly. Extracts have been further used to demonstrate a moonlighting regulatory role for nuclear import receptors or importins on these cell cycle assembly events. Here we show that exportins can also play a role in these events. Addition of Crm1, Exportin-t, or Exportin-5 decreased nuclear pore assembly in vitro. RanQ69L-GTP, a constitutively active form of RanGTP, ameliorated inhibition. Both Crm1 and Exportin-t inhibited fusion of nuclear membranes, again counteracted by RanQ69L-GTP. In mitotic extracts, Crm1 and Exportin-t negatively impacted spindle assembly. Pulldowns from the extracts using Crm1- or Exportin-t-beads revealed nucleoporins known to be essential for both nuclear pore and spindle assembly, with RanQ69L-GTP decreasing a subset of these target interactions. This study suggests a model where exportins, like importins, can regulate major mitotic assembly events.